Comparison of fatigue crack propagation behaviour in two gas turbine disc alloys under creep-fatigue conditions: evaluating microstructure, environment and temperature effects. (1st July 2013) - Everitt, S; Jiang, R; Gao, N; Starink, M J; Brooks, J W; Reed, P A S
<x xml:space="preserve">Abstract</x> Gas turbine disc materials should possess excellent fatigue and creep performance due to the severe in service conditions experienced. In this study, a comparison of fatigue crack propagation behaviour in two turbine disc alloys, i.e. N18 and low solvus high refractory (LSHR) superalloy, has been made in terms of the propagation rate and fractography observed under equivalent testing conditions. Temperatures of 650 and 725°C are compared for a trapezoidal dwell fatigue cycle (1-20-1-1) in both air and vacuum at an R ratio of 0·1. It is found that coarse grained LSHR superalloy has better fatigue crack propagation resistance than fine grained N18 in vacuum, which is ascribed to its better creep performance. Oxidation causes significant degradation of fatigue performance of these two alloys, especially in the LSHR superalloy at higher temperature (725°C), resulting in its inferior fatigue performance compared with N18. In the LSHR superalloy, it seems that oxidation is the principal contributor to the deterioration of fatigue resistance. This is supported by observations of transgranular fracture in vacuum and intergranular fracture in air. In contrast, creep is a greater contributor to the deterioration in fatigue performance of N18 (as indicated by the intergranular failure modes observed in vacuum). An apparent activation energy analysis is able to provide further insight into the underlying mechanisms of fatigue crack propagation under creep-oxidation-fatigue conditions in these two alloys.